Construction and validation of a non- verbal test to measure some science concepts among preschoolers - Malaga, Irene G. (1977)
In this study, the researcher constructed and evaluated a 30-item test to measure some sciene concepts among preschoolers. For editing as well as for checking the items were presented to some co-MAT participants and to a science specialist. An informal interview with some preschoolers was conducted to ensure that the options were what the illustrations represented.